TEKNIK COGNITIVE BEHAVIOR THERAPY (CBT) DALAM GANGGUAN KEPRIBADIAN BIPOLAR - Aji Restu Sauran; Wandrio Salewa (POIMEN Jurnal Pastoral Konseling, 2022)
Bipolar is a form of mental disorder that refers to mood disorders that include emotional disorders that make a person not perform their life functions properly where the sufferer will experience sadness from the phase of depression to euphoria and unrealistic in the mania phase. The goal of the study was to outline how cognitive behavior therapy (CBT) approaches play a role in bipolar disorder as well as counseling techniques through cognitive behavior therapy approaches. Research is done through literature studies by collecting relevant data from books, journals, magazines, and so on. The result of this study is that CBT is present to change the perception of a wrong mindset about a sufferer who has an impact on maladaptive behavior, using CBT techniques, namely: supportive guidance, positive thinking therapy, Socratic method, and thought stopping.